ANALISIS KEMAMPUAN LITERASI MEMBACA SISWA KELAS V DI SD NEGERI 004 LUMBIS - Mulyani, Chatrin; Adiasti, Nindya; Bua, Mety Toding; Agustina, Degi Alrinda (Jurnal Pendidikan Dasar Borneo (Judikdas Borneo), 2024)
This research aims to describe the results of the reading literacy skills of class V students at SD Negeri 004 Lumbis. This research uses descriptive qualitative research. A total of 8 fifth grade students participated in the research and took a reading literacy ability test, which was then grouped based on the categories of high, medium and low reading literacy ability. After that, the researcher selected 3 students representing each category of reading literacy ability to be interviewed. The research results show that (1) Subjects in the high category are able to find explicit information, identify changes in intrinsic elements, infer feelings and character traits, draw up inferences, compare characterizations, assess the suitability of illustrations, and reflect knowledge well. When solving AKM reading literacy questions, the subject experienced difficulties because he was not careful in choosing answers. (2) Subjects in the medium category are able to find explicit information, identify changes in intrinsic elements, infer feelings and character traits, compare characterizations, assess the suitability of illustrations, and reflect knowledge well. When solving AKM reading literacy questions, the subject experienced difficulties due to not understanding the content of the reading, not being careful in choosing answers, and not being able to determine the main idea in the reading.